Trust and Openness in Visual Communication: An Augmented Reality Analysis - Risa Amalia (Jurnal Multidisiplin Sahombu, 2025)
Augmented Reality (AR) is a technology that integrates virtual elements into the real world, creating a more immersive, interactive experience. This technology is increasingly used in various fields, including education, business, and communications. This study, entitled " Augmented Reality and Its Effect on Trust and Openness in Visual Communication," aims to determine the impact of augmented reality technology on visual communication. reality (AR) on trust and openness Visual communication. A qualitative approach was used in this study, with the participation of 20 students from Sultan Syarif Kasim State Islamic University, Riau. Observations and interviews were conducted to obtain empirical data. This study shows that AR can increase trust through more realistic visualizations and more personalized interactions. Furthermore, AR also increases openness by enabling more transparent and emotional information delivery. This technology has proven effective in improving understanding and involvement, especially in environment education and business presentations. Therefore, these results confirm the great potential of AR in improving the quality of visual communication and making a positive contribution in various fields of application.